2012
DOI: 10.1371/journal.pone.0041751
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Investigation of Falciparum and Vivax Malaria for Identification of Surrogate Protein Markers

Abstract: This study was conducted to analyze alterations in the human serum proteome as a consequence of infection by malaria parasites Plasmodium falciparum and P. vivax to obtain mechanistic insights about disease pathogenesis, host immune response, and identification of potential protein markers. Serum samples from patients diagnosed with falciparum malaria (FM) (n = 20), vivax malaria (VM) (n = 17) and healthy controls (HC) (n = 20) were investigated using multiple proteomic techniques and results were validated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 45 publications
3
69
0
Order By: Relevance
“…Interestingly, there is a negative correlation between total heme and hemopexin levels in malaria, suggesting that during infection, mainly unbound heme is found in plasma. Hemopexin is a positive acute-phase protein, and previous studies have reported an increase in the circulating levels of hemopexin and its precursor during sepsis or in MM (23,24). However, decreased levels of hemopexin during severe sepsis also were associated with a low survival prognosis, highlighting the importance of hemopexin in the scavenging of free heme (23,25).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is a negative correlation between total heme and hemopexin levels in malaria, suggesting that during infection, mainly unbound heme is found in plasma. Hemopexin is a positive acute-phase protein, and previous studies have reported an increase in the circulating levels of hemopexin and its precursor during sepsis or in MM (23,24). However, decreased levels of hemopexin during severe sepsis also were associated with a low survival prognosis, highlighting the importance of hemopexin in the scavenging of free heme (23,25).…”
Section: Discussionmentioning
confidence: 99%
“…Patients co-infected with any other infectious diseases or other plasmodial infections such as vivax malaria or mixed infections (infected with both P. falciparum and P. vivax) were excluded from this study. Sample collection, serum separation, and storage were performed following the same protocol as reported earlier [13]. Serum samples were stored as multiple aliquots and uniformity was maintained in terms of number of freeze/thaw cycles while selection of the test (NSFM/SFM) and control (HC) samples for the comparative proteomic analysis to minimize the pre-analytical variables.…”
Section: Subject Recruitment Blood Collection and Serum Separationmentioning
confidence: 99%
“…However, there is a dearth of similar proteomic analysis of severe falciparum malaria in Indian populations. In an earlier study we have reported the modulations in human serum proteome and various physiological pathways in uncomplicated non-severe falciparum malaria in an adult population from India [13]. In this study, serum samples from adult severe and non-severe falciparum malaria (SFM and NSFM) patients along with healthy community controls from three different endemic regions of India were investigated using 2D-DIGE and iTRAQbased quantitative proteomics in combination with ESI-Q-TOF and QExactive mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic analyses have identified signatures that distinguish Plasmodium falciparum malaria, Plasmodium vivax malaria, healthy controls, and leptospirosis with 95% accuracy (Ray et al, 2012). Thirty serum proteins distinguished P. falciparum from healthy controls, 31 proteins distinguished P. vivax from healthy controls, and 13 were differentially expressed when comparing the two malarial subtypes.…”
Section: Malariamentioning
confidence: 99%